Fish, Omega-3 and human health - Lands, William E. M., 1930- (AOCS Press, 2005)
Dr. Lands expertly explains how curative/treatment interventions have unsuccessfully prevented diseases by ignoring the initial dietary causes of disease and death. With years of clinical and dietary expertise, he uses clear examples and current data to demonstrate how a moderate, balanced diet is the key to long-term good health. This edition includes an expanded glossary of words and concepts to help readers recognize how specific nutrient imbalances in our normal diets can contribute to disease and death. Also new to this edition are dietary tables showing the link between diet choices and the levels of healthy omega-3 in the body. As Dr. Lands eloquently states, "Curiosity is the beginning of understanding, and a steady pursuit of our questions seems to always lead us into new adventures and new understandings."The second edition of Fish, Omega-3 and Human Health reaffirms that the essential fatty acids in the foods we eat form hormones that have powerful effects on human life. While many find it hard to believe that a simple change of diet can affect so many aspects of their lives, this book aims to shift prevailing attitudes about the relationship between foods and disease.